Kunst als (botanisches) Studium der Natur? Bemerkungen zu Goethes Schrift «Einfache Nachahmung der Natur, Manier, Stil»: [Art as (botanical) study of nature? Notes on Goethe’s essay «Simple imitation of nature, manner, style»] (Studia theodisca, 2022)
Goethe’s essay Einfache Nachahmung der Natur, Manier, Stil is steeped in an analogy: The life science of botany serves as an aesthetic foil, botany and art are set in parallel – to show how Goethe develops this, and what it implies, is the aim of this paper.